2021
DOI: 10.11648/j.ijee.20210601.13
|View full text |Cite
|
Sign up to set email alerts
|

Review on Reproductive and Productive Performance of Dairy Cow in Ethiopia

Abstract: Ethiopia has largest livestock population in Africa. Despite the largest cattle population, its productive and reproductive performance is very low productivity is relationship between inputs and outputs. The information about reproductive and productive performance in Ethiopia is limited for smallholder. Therefore; the objective of this review paper was to highlight the overall aspects of reproductive and productive performance parameters under Ethiopian condition. Reproductive performance is a trait of outst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 4 publications
1
3
0
Order By: Relevance
“…Previous studies on Thai-Holstein crossbred cattle reported an average AFC value of 32.39 ± 5.76 and 30.97 ± 6.65 months [26,27], higher than the recommended age. The same results were reported in Friesian × Zebu (F1), and Friesian × Arsi (F1) cattle were obtained as 35.3 and 33.9 months, respectively [25]. The lower values of AFC reported in US dairy cattle were 24.5 ± 2.73 months for Holstein, 22.9 ± 2.74 months for Jersey, and 26.3 ± 3.13 months for Brown Swiss [28].…”
Section: Reproductive Traits In Dairy Cattlesupporting
confidence: 79%
See 3 more Smart Citations
“…Previous studies on Thai-Holstein crossbred cattle reported an average AFC value of 32.39 ± 5.76 and 30.97 ± 6.65 months [26,27], higher than the recommended age. The same results were reported in Friesian × Zebu (F1), and Friesian × Arsi (F1) cattle were obtained as 35.3 and 33.9 months, respectively [25]. The lower values of AFC reported in US dairy cattle were 24.5 ± 2.73 months for Holstein, 22.9 ± 2.74 months for Jersey, and 26.3 ± 3.13 months for Brown Swiss [28].…”
Section: Reproductive Traits In Dairy Cattlesupporting
confidence: 79%
“…Age at First Calving (AFC) AFC is the age at which heifers first calve and is also known as the start of the heifer's productive life [23,24]. AFC influences the lifetime production, reproduction of the female, milk production, and lifetime calf crop [25]. Indirectly, AFC affects the cost invested for rearing cattle.…”
Section: Reproductive Traits In Dairy Cattlementioning
confidence: 99%
See 2 more Smart Citations